The State, Religion, and Ethnic Politics: Pakistan, Iran and Afghanistan. Edited by Ali Banuazizi and Myron Weiner. Syracuse University Press (1407 AH/1987 AC). Published simultaneously by Vanguard Books Ltd. , Pakistan. pp. 390. (American Journal of Islam and Society, 1988)
As the ideas of struggle against imperialism and class were prominentamong social scientists a generation ago, those of ethnicity are in the forefronttoday. Ethnicity-language, race, folk culture, food, etc., cut across classand sect. In Africa and Asia it has assumed violent political shape, succeedingin creating nations like Bangladesh or seriously disrupting them as in thecase of (Sri Lanka).The interrelationship of ethnicity with the state and religion are exploredin Pakistan, Iran and Afghanistan in the book. It is the very fuzziness ofthese central concepts - state, religion, ethnicity - that creates so much heataround their discussion. The theoretical linkages between the concepts inthese three states are clear. Not so clear is the method to resolve tensionsbetween them. A book, then, which brings together “an outstanding groupof anthropologists, historians, political scientists and Islamicists” promisesvalue.Fourteen distinguished academics have combined to produce the contentsof the book. Some cannot resist the pitfall into which social scientists arewont to plummet, i.e., the use of impenetrably recondite jargon: “Whateverthe particular criterion for group identity, inquiry into the relationship ofethnic groups to the larger sociocultural systems of which they are a partought to rest on the ‘situational’ approach to ethnicity” (P. Higgins: p.169).Mercifully this kind of language is restricted.African and Asian scholars will be quick to apply the label “Orientalist”to some of the participants. Others will note that the 4 authors of the chapterson Pakistan are non-Muslims; an observation not entirely irrelevant abouta book on ethnicity and religion. This kind of emotionalism however, mustnot be allowed to distract from the quality of the work. The papers are scholarly,and most are based on a life-time’s work. They attempt to discuss the centralissues in complex and changing societies.The editors, in a comprehensive and useful introduction, lay out their ...